Gene transfer system for Rhodopseudomonas viridis. - Lang, F S (1989)
A gene transfer system for Rhodopseudomonas viridis was established which uses conjugation with Escherichia coli S17-I as the donor and mobilizable plasmids as vectors. Initially, plasmids of the incompatibility group P1 (pRK290 and pRK404) were used. The more effective shuttle vectors between E. coli and R. viridis, pKV1 and pKVS1, were derived from plasmid pBR322 and showed the highest conjugation frequency (10(-2] thus far demonstrated in purple bacteria. It was also demonstrated that Rhizobium meliloti can be used as a donor for conjugation with R. viridis. From a genomic cosmid library of R. viridis constructed in the vector pHC79, clones that coded for subunits H (puh operon), L, M and cytochrome c (puf operon) of the photosynthetic reaction center were isolated and characterized. For linkage of the two operons on the genome, cosmids that overlapped with the operon-carrying clones were identified. The relative positions of the two operons could not be determined, but the operons must be more than 100 kilobase pairs apart. Thus, the genomic organization of the reaction center in R. viridis is different from that of Rhodobacter capsulatus, for which a distance of about 39 kilobase pairs was determined. From a spontaneous mutant of R. viridis that is resistant to the herbicide terbutryn, the puf operon was cloned in pKVS1 and transferred by conjugation into R. viridis wild-type cells. The resulting exconjugants were resistant to the herbicide, which demonstrated that the puf operon on pKVS1 constructions was functionally expressed in R. viridis.